Drone piloting - Simmons, Curt (John Wiley & Sons, Inc., 2025)
The know-how you need to become a pro drone pilot and market your skill. Licensed and skilled drone pilots are in huge demand. Drone Piloting For Dummies teaches you how to make a career out of it. From real estate to construction to inspection to mapping to delivery, the need for drone photography and videography is everywhere. This book outlines the basics of selecting and operating a drone, shows you how to get licensed, and explains all the regulations you need to know. You'll also learn to read charts and capture high-quality photos and videos. Plus, this guide walks you through the process of turning this skill into a full-time career or profitable side hustle. Written by a licensed drone pilot and entrepreneur, Drone Piloting For Dummies helps you take off on your new adventure! Grasp flying basics and care for your drone ; Prep for certification and learn the regulations ; Refine your photography and videography skills ; Market your skills and discover cool career opportunities. This book is for anyone who wants to become a drone pilot or increase their piloting skills for job readiness and performance
Keywords: Operator; Technik; Luftfahrtrecht; Drohne -- Flugkörper; Flugführung; Drone aircraft; Drone aircraft pilots